PROSES PENYUSUNAN ANGGARAN PADA DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KABUPATEN SLEMAN YOGYAKARTA - Putra, Indra Mahardika (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
The purpose of this research is to find out the stages of the process of drafting the Regional Working Unit Budget Work Plan or in Indonesia called the Working Plan of Regional Working Unit Budget (RKA-SKPD) and what strategy is used by the regional apparatus unit or in Indonesia called the Regional Device Work Unit (SKPD) in budgeting. The research method is quantitative descriptive with data type is primary data and secondary data with data collection technique of interview and observation. The results of the study that (a). budget drafting process In Sleman District Youth and Sports Education Office has been in accordance with the Government Regulation of Finance Minister Regulation No 92 PMK.05, (b). Weak process of evaluation and monitoring of the program resulting in constraints on the process of delay in the disbursement of funds Keywords: Preparation of Regional Budget Work Plan(RKA-SKPD)